Analisis Morfologis Verba آمَنَ dalam Qs. Al-Baqarah Ayat 285: Kajian Wazn Berbasis Teori Ibn Faris - Lasmiati Radiah; Baiq Intan Amalia; Teddy Nur Hidayat; H. Akhmad Dasuki (JOURNAL SAINS STUDENT RESEARCH, 2026)
Abstract. Linguistic analysis of the Qur'an represents one of the most significant approaches to understanding divine messages in depth. Among the branches of Arabic linguistics that play a major role in interpreting Qur'anic meaning is morphology (ilmu sharaf), the study of word structure and the semantic changes produced by alterations in word form. Within the Qur'an, verbs occupy a central position as the primary elements conveying action and the core meaning of a verse. One verb that merits particular examination is āmana (آمَنَ) in QS. Al-Baqarah verse 285, as it is directly related to the concept of faith (iman) in Islam. This study aims to analyze the morphological form of the verb āmana using Ibn Faris's wazn theory as the primary analytical framework. Ibn Faris, through his work Maqayis al-Lughah, emphasizes the relationship between a root word and its fundamental meaning. The research employs a qualitative approach through library research, drawing on classical sharaf texts, Arabic dictionaries, Qur'anic commentary (tafsir), and relevant academic journals. The study focuses on identifying the morphological form of the verb, its wazn pattern, and its semantic implications for the meaning of the verse. The findings reveal that the verb āmana is a fi'il mazid following the pattern af'ala (أَفْعَلَ). The addition of a hamzah at the beginning of the word shifts the meaning from amina (أَمِنَ) to "to believe" or "to have faith." Semantically, this form conveys an active and conscious engagement in the process of belief. These findings demonstrate that morphological analysis grounded in wazn theory can serve as a valuable approach to understanding the relationship between linguistic structure and theological meaning in the Qur'an. Abstrak. Kajian linguistik terhadap Al-Qur'an merupakan salah satu pendekatan penting dalam memahami pesan-pesan ilahi secara mendalam. Salah satu cabang linguistik Arab yang berperan besar dalam memahami makna Al-Qur'an adalah morfologi atau ilmu sharaf, yaitu ilmu yang mengkaji struktur kata dan perubahan makna yang ditimbulkan oleh perubahan bentuk kata tersebut. Dalam Al-Qur'an, verba memiliki posisi penting karena menjadi unsur utama yang menggambarkan tindakan dan makna inti suatu ayat. Salah satu verba yang menarik dikaji adalah verba آمَنَ dalam QS. Al-Baqarah ayat 285 karena berkaitan langsung dengan konsep keimanan dalam Islam. Penelitian ini bertujuan untuk menganalisis bentuk morfologis verba آمَنَ dengan menggunakan teori wazn Ibn Faris sebagai kerangka analisis utama. Ibn Faris melalui Maqayis al-Lughah menekankan hubungan antara akar kata dan makna dasarnya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka melalui kitab sharaf, kamus Arab klasik, kitab tafsir, dan jurnal ilmiah yang relevan. Fokus penelitian diarahkan pada identifikasi bentuk morfologis verba, pola wazn, dan implikasi semantisnya terhadap makna ayat. Hasil penelitian menunjukkan bahwa verba آمَنَ merupakan fi‘il mazid yang mengikuti wazn أَفْعَلَ. Penambahan hamzah pada awal kata menghasilkan perubahan makna dari أَمِنَ menjadi “beriman” atau “mempercayai”. Secara semantis, bentuk tersebut menunjukkan makna tindakan aktif dan kesadaran dalam proses keimanan. Temuan ini menunjukkan bahwa analisis morfologis berbasis teori wazn dapat menjadi pendekatan penting dalam memahami hubungan antara struktur bahasa dan makna teologis dalam Al-Qur’an.